STUDENT PERCEPTIONS ON ENGLISH PRONUNCIATION AFTER TAKING COURSE PHONETICS AND PHONOLOGY - Yousef Bani Ahmad (Universitas Singaperbangsa Karawang, 2018)
This study aims to find out how students' perceptions of pronunciation after getting the subject of phonetics and phonology. To answer the formulation of this problem, researcher used a qualitative descriptive approach. Subjects in this study are students of English Education University Singaperbangsa Karawang who have taken the course. The data of this study were obtained from questionnaires were given to six students as respondents. The results of this study indicates that respondents have the same perception that English learners are greatly assisted by phonetics and phonology courses in improving pronunciation, reducing pronunciation mistakes, being able to read phonetics transcription in the dictionary and also increase confidence when speaking English both in and out of class.